Does excessive social media use decrease subjective well-being? A longitudinal analysis of the relationship between problematic use, loneliness and life satisfaction - Marttila Eetu; Koivula Aki; Räsänen Pekka (Elsevier B.V., 2022)
Current literature suggests problematic social media use (PSMU) predicts reduced social and psychological well-being. Lonely people are more prone to experience the negative outcomes of PSMU, but only few studies have focused explicitly on how loneliness affects the relationship between PSMU and subjective well-being experiences. In this paper, we examine if loneliness influences the association between PSMU and life satisfaction. We used nationally representative cross-sectional data from Finnish social media users (N = 2991) and follow-up panel data (N = 2021). First, we tested if PSMU affects satisfaction with life indirectly through loneliness while controlling for a set of background variables. Next, we examined whether changes in PSMU and loneliness affect life satisfaction over time. First analyses showed that PSMU was associated with life satisfaction negatively, but the effect was largely confounded by loneliness. Longitudinal analysis revealed increased PSMU did not predict decreased satisfaction with life within individuals, but increased PSMU predicted increased loneliness, and increased loneliness predicted decreased satisfaction with life. The analyses indicate that loneliness is a crucial element that contributes to the relationship between PSMU and life satisfaction. In addition, earlier observations that PSMU might increase loneliness over time were confirmed.